Variasi Pencampuran Tepung Buah Gayam (Inocarpus Fagifer L.Forst) dalam Pembuatan Bolu Kukus Ditinjau dari Uji Organoleptik - Agustina, Riski Zada; Kirani, Risna Dwi; Lestari, Catur Retno (Indonesian Journal of Nutrition Science and Food; Vol 3 No 2 (2024): Januari 2024, 2024)
Gayam is a plant native to Indonesia which is widespread in several regions under different names. Gayam flour was chosen because it can be used as an alternative and supports food diversification programs by reducing dependence on cereal-based wheat flour. Gayam steamed cake is made by adding wheat flour and gayam flour. The aim of this research was to determine the effect of replacing wheat flour with style flour in terms of organoleptic tests. The research method used RAL (Completely Randomized Design) with 4 limited treatments  of Gayam steamed cake with 2 repetitions, so that 8 experimental units were obtained. There are 4 treatments to make Gayam steamed cakes with the addition of wheat flour and Gayam flour, respectively P1, namely 100%:0%, is used as a control, P2 85%:15%, P3 70%:30%. , and P4, or 55%: 45%. The results of statistical analysis were tested using one-way analysis of variance (ANOVA) with a confidence level of 95%. The results of the analysis of color preferences were highest in the control variation and lowest in the 45% variation, aroma preferences were highest in the control variation and lowest in the 15% variation, texture preferences were highest in the control variation and lowest in the control variation. 45% variation. control variations. control variations. 45% variation, the highest taste preference is in the control variation and the lowest is in the 15% variation. Gayam flour has not been able to replace wheat flour, either partially or completely. There were significant differences in color and texture p=<0.05, but there were no significant differences in taste and aroma.